2009
DOI: 10.1007/s11011-009-9157-2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise increases BDNF levels in the striatum and decreases depressive-like behavior in chronically stressed rats

Abstract: Early life stress in humans can affect the development of neurons and neurotransmitter systems and predispose an individual to the subsequent development of depression. Similarly, in rats, maternal separation causes anxiety and depressive-like behavior and decreased corticosterone levels. Patients receiving pharmacological treatment for depression often experience negative side-effects or do not respond optimally and therefore the use of exercise as alternative antidepressant treatment is investigated. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(100 citation statements)
references
References 56 publications
9
91
0
Order By: Relevance
“…Though, one of the mechanisms observed with CBT, tailored to the needs of each patient, is the power to produce volumetric changes in the amygdala, in the case of chronic anxiety [48]. Human studies have shown that a deficiency in the availability of BDNF is associated with vulnerability to depression [49] and this deficiency is reduced after 30 minutes of exercise in patients with panic disorder but not in healthy controls [50] Another mechanism is influenced by exercise Increased the brain growth factor such as brainderived neurotrophic factor (BDNF) expression is related to the effects of exercise on brain plasticity, cognitive functioning and health [51,52].…”
Section: Neurobiological Mechanismsmentioning
confidence: 99%
“…Though, one of the mechanisms observed with CBT, tailored to the needs of each patient, is the power to produce volumetric changes in the amygdala, in the case of chronic anxiety [48]. Human studies have shown that a deficiency in the availability of BDNF is associated with vulnerability to depression [49] and this deficiency is reduced after 30 minutes of exercise in patients with panic disorder but not in healthy controls [50] Another mechanism is influenced by exercise Increased the brain growth factor such as brainderived neurotrophic factor (BDNF) expression is related to the effects of exercise on brain plasticity, cognitive functioning and health [51,52].…”
Section: Neurobiological Mechanismsmentioning
confidence: 99%
“…In all the 12 studies, the scholars agreed in unison that synapsin I plays a significant role in initiating the intracellular signaling mechanism. In one study, 1 week long of enforced physical exercise has the capacity of improving the social memory in a characteristically troubling dimensional activity appertaining to the augmentation of the corresponding to the manifestation of the brain derivative neurological factor in the dentate gyrus, hippocampus, and the perirhinal cortex [12]. The other studies revealed that the administration of a single dosage of BDNF in the intracellular cerebral ventricle is adequate to emulate the developments in the object identification.…”
Section: Resultsmentioning
confidence: 99%
“…Human studies have shown that a deficiency in the availability of BDNF is associated with vulnerability to depression [85]. The Increased the brain growth factor such as BDNF expression is related to the effects of exercise on brain plasticity, cognitive functioning and health [27,58].…”
Section: Neurobiological Mechanismsmentioning
confidence: 99%